Combination of phototherapeutic keratectomy and wavefront-guided photorefractive keratectomy for the treatment of Thiel–Behnke corneal dystrophy - Hsiao, Chia-Chieh (Indian J Ophthalmol, 2017)
Phototherapeutic keratectomy (PTK) has been used to treat anterior corneal dystrophy but may cause hyperopic shift or corneal high-order aberration. We describe the successful treatment of a case of a 43-year-old female with Thiel–Behnke corneal dystrophy, using PTK followed by wavefront-guided photorefractive keratectomy (PRK). The patient had high corneal aberration and hyperopic shift after PTK in both eyes. The corneal surface regularity index and surface asymmetric index increased after PTK and decreased after wavefront-guided PRK. Vision improved from preoperative 20/400 and 20/60 to postoperative 20/20 and 20/25 in the right eye and the left eye, respectively. Additional wavefront-guided PRK may enhance the effects of PTK by reducing irregular corneal surfaces and by correcting PTK-induced hyperopic shift.